Highlights 2020 - Yearly status report EDEN Initiative - Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent (2020)
What a year, what a year! Who would have thought this?! The year 2020 marked the beginning of a global pandemic that impacted all areas of social- and professional life. Beginning of mid-March, DLR went into a complete lock-down, followed only by partial reopening during summer, entering a soft lock-down again in winter 2020. Although these extreme circumstances were not favourable, the operation of the EDEN ISS facility in Antarctica continued successfully, and multiple new research projects were initiated by the group throughout the year. Most notable is the collaborative science mission of NASA and DLR to jointly operate the EDEN ISS greenhouse. In December 2020, NASA scientist Jess Bunchek travelled to Antarctica. She operates the facility for the isolation campaign in 2021. A multifaceted research programme was worked out between NASA and the EDEN group, which includes e.g. cultivar testing, and crew time measurements. The year 2020 also marked a milestone for the EDEN group, by outlining the research and development goals for the next decade. The DLR roadmap for the development of bio-regenerative life support systems was officially published. The plan foresees the development of a 1:1 life support module by the year 2025 that will allow to test key cultivation technologies already on space-rated system design level. This will push the courageous ambition to have a flight-ready design by 2030 for a possible Moon deployment scenario.